Influence of Siamese Pumpkin (Sechium Edule) Stew on Decreased Blood Sugar Levels Type II Diabetes Mellitus Patients In the Work Area of Cempaka Health Center, Banjarmasin - Era Widia Sary; Rini Maulida (Health Media, 2019)
Currently Fitofarmaka therapy is popular among the people because it is considered as a treatment that has few side effects, cheap, and easy to obtain one of which is by conjoined pumpkin therapy. In Patients with Type II Diabetes Mellitus in the Work Area of ​​Cempaka Health Center, Banjarmasin. This type of research is Quasy-experiment with Pre-Test and Post-Test Non Equivalent Control Group design, the sampling technique is purposive sampling. Data analysis uses Paired Sample T-Test and Independent Sample Sample T-Test with a significance limit α = 0.05. Conjuring boiled pumpkin for 7 days in the intervention group was obtained. For patients with type II Diabetes mellitus, they can choose an alternative treatment besides pharmacological therapy, namely by using Siam Pumpkin which is processed by boiling.